Factors associated with high density lipoprotein cholesterol dyslipidemia in quilombolas (Research, Society and Development, 2020)
The present study aimed to analyze the prevalence of high-density lipoprotein (HDL-c) cholesterol dyslipidemia and associated factors in the quilombola population in Bahia. This is a population-based study, with 850 adults of both sexes. HDL-c dyslipidemia was determined to be